2012
DOI: 10.1148/radiol.12112061
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of Hepatic Uptake Transporter Function in Healthy Subjects by Using Gadoxetic Acid–enhanced MR Imaging

Abstract: Purpose:To determine if genetic polymorphisms of liver-specific human organic anion transporting polypeptide (OATP) 1B1 and OATP1B3 influence cellular uptake of gadoxetic acid in vitro and if functionally relevant polymorphisms are confounders for liver enhancement by gadoxetic acid in healthy subjects. Materials and Methods:This study received ethics approval, and all subjects provided written informed consent. Cellular uptake of gadoxetic acid by OATP1B1 and OATP1B3 and their frequent genetic variants was me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
89
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(95 citation statements)
references
References 36 publications
6
89
0
Order By: Relevance
“…Gd-EOB-DTPA is mainly incorporated into hepatocytes by organic anion transporting polypeptide (OATP) 1B3 and its uptake rate significantly correlates with OATP1B3 expression in normal hepatocytes and HCC cells [33,34]. OATP1B3 is predominantly expressed in hepatocytes distributed around zone III in normal liver parenchyma [35].…”
Section: Mri Of Rild and Focal Liver Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…Gd-EOB-DTPA is mainly incorporated into hepatocytes by organic anion transporting polypeptide (OATP) 1B3 and its uptake rate significantly correlates with OATP1B3 expression in normal hepatocytes and HCC cells [33,34]. OATP1B3 is predominantly expressed in hepatocytes distributed around zone III in normal liver parenchyma [35].…”
Section: Mri Of Rild and Focal Liver Injurymentioning
confidence: 99%
“…Radiation-induced hepatitis is described as "radiation hepatitis", "radiation-induced hepatic toxicity", "radiation-induced liver damage", and "radiation-induced liver disease (RILD)". RILD, which describes clinical and pathological features [1][2][3][4], refers to the severity of liver toxicity after high-dose radiotherapy delivered to large liver volumes or when the whole-liver tolerance dose (30)(31)(32)(33)(34)(35) is exceeded during external beam radiotherapy (RT).…”
Section: Introductionmentioning
confidence: 99%
“…The magnetic resonance imaging agent gadoliniumethoxybenzyl-diethylenetriamine pentaacetic acid (Gd-EOB-DTPA) is also shown to be transported by OATP1B1 and OATP1B3 (33)(34)(35). In a retrospective study involving 22 Due to the limited number of references that can be cited in this review, Table I does not include original references, but details can be found in the recent reviews (7,8) and references therein OATP organic anion-transporting polypeptide, DHEA-S dehydroepiandrosterone sulfate, Gd-EOB-DTPA gadolinium-ethoxybenzyldiethylenetriamine pentaacetic acid patients with hepatic cancer, high OATP1B3 expression levels were significantly correlated with increased uptake of Gd-EOB-DTPA (33).…”
Section: Role Of Oatps In the Disposition Of Substra Tes Implicated Imentioning
confidence: 99%
“…In a retrospective study involving 22 Due to the limited number of references that can be cited in this review, Table I does not include original references, but details can be found in the recent reviews (7,8) and references therein OATP organic anion-transporting polypeptide, DHEA-S dehydroepiandrosterone sulfate, Gd-EOB-DTPA gadolinium-ethoxybenzyldiethylenetriamine pentaacetic acid patients with hepatic cancer, high OATP1B3 expression levels were significantly correlated with increased uptake of Gd-EOB-DTPA (33). In individuals carrying certain genetic variations associated with decreased OATP1B1 activity, the liver enhancement by the gadolinium-based imaging agent was substantially attenuated (35). These findings suggest that the activity of OATPs and genetic variations may be potential confounders leading to a reduced signal intensity in liver magnetic resonance imaging.…”
Section: Role Of Oatps In the Disposition Of Substra Tes Implicated Imentioning
confidence: 99%
“…It is a gadolinium chelate that is actively taken up into the hepatocytes through the organic aniontransporting polypeptides [15]. This is a property Gd-EOB-DTPA shares with the iminodiacetic acid compounds used in hepatobiliary scintigraphy (HBS) and with indocyanine green (ICG) [16][17][18][19][20].…”
mentioning
confidence: 99%